Fiber Bragg grating based sensing system: Early corrosion detection for structural health monitoring - Tan C.H.; Shee Y.G.; Yap B.K.; Adikan F.R.M. (Elsevier B.V., 2023)
Bragg gratings; Coatings; Corrosion; Corrosion prevention; Corrosion rate; Fiber optic sensors; Fiber optics; Fibers; Medical applications; Microchannels; Polydimethylsiloxane; Silicones; Structural health monitoring; Biomedical applications; Bragg wavelength shift; Corrosion detection; Corrosion monitoring; Polydimethylsiloxane PDMS; Structural health monitoring (SHM); Wavelength shift; Weight loss measurements; Fiber Bragg gratings